Attitudes and practices towards HPV vaccination and its social processes in Europe: An equity-focused scoping review - Alarcão, V. (2022)
The sociological understanding of the human papillomavirus (HPV) vaccination offers the possibility to understand society better as the processes that shape health beliefs and influence HPV vaccine decisions relate to gender, power, and identity. This research aimed to locate, select, and critically assess scientific evidence regarding the attitudes and practices towards HPV vaccination and its social processes with a focus on health equity. A scoping review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews (PRISMA-ScR) and the recommendations made by the Joanna Briggs Institute was undertaken. Medline and Scopus were searched from their start date until December 2021. The review followed the Population/Concept/Context (PCC) inclusion criteria: Population = General population, adults and adolescents, Concept = Empirical data on determinants of HPV vaccination, Context= Studies on attitudes and practices towards HPV vaccination and its social processes with a focus on gender, class, and ethnic/racial inequalities. Of the 235 selected articles, 28 were from European countries and were the focus of this review, with special attention to socio-economic determinants in HPV vaccine hesitancy in Europe, a region increasingly affected by vaccination public distrust and criticism. Barriers and facilitators of HPV vaccine uptake and determinants of immunization were identified. Given the emphasis on health equity, these data are relevant to strengthening vaccination programs to promote vaccination for all people.